Systematic review: pain, cognition, and cardioprotection—unpacking oxytocin’s contributions in a sport context - Szabó, Péter; Bonet, Sara; Hetényi, Roland; Hanna, Dániel; Kovács, Zsófia; Prisztóka, Gyöngyvér; Križalkovičová, Zuzana; Szentpéteri, József (Frontiers in Physiology, 2024)
This systematic review investigates the interplay between oxytocin and exercise; in terms of analgesic, anti-inflammatory, pro-regenerative, and cardioprotective effects. Furthermore, by analyzing measurement methods, we aim to improve measurement validity and reliability.Utilizing PRISMA, GRADE, and MECIR protocols, we examined five databases with a modified SPIDER search. Including studies on healthy participants, published within the last twenty years, based on keywords "oxytocin", "exercise" and "measurement", 690 studies were retrieved initially (455 unique records). After excluding studies of clinically identifiable diseases, and unpublished and reproduction-focused studies, 175 studies qualified for the narrative cross-thematic and structural analysis.The analysis resulted in five categories showing the reciprocal impact of oxytocin and exercise: Exercise (50), Physiology (63), Environment (27), Social Context (65), and Stress (49).Exercise-induced oxytocin could promote tissue regeneration, with 32 studies showing its analgesic and anti-inflammatory effects, while 14 studies discussed memory and cognition. Furthermore, empathy-associated OXTR rs53576 polymorphism might influence team sports performance. Since dietary habits and substance abuse can impact oxytocin secretion too, combining self-report tests and repeated salivary measurements may help achieve precision.Oxytocin's effect on fear extinction and social cognition might generate strategies for mental training, and technical, and tactical development in sports. Exercise-induced oxytocin can affect the amount of stress experienced by athletes, and their response to it. However, oxytocin levels could depend on the type of sport in means of contact level, exercise intensity, and duration. The influence of oxytocin on athletes' performance and recovery could have been exploited due to its short half-life. Examining oxytocin's complex interactions with exercise paves the way for future research and application in sports science, psychology, and medical disciplines.